Study on Characteristics of SAR Data in Ravine Reservoir Area - Mowen Xie; Jiaxuan Huang; Jiehui Huang (Institute of Advanced Engineering and Science, 2016)
Landslide monitoring is one of the most important methods in landslide prevention. Landslide early identifying that based on D-InSAR technique is one of the effective means in landslide monitoring in ravine reservoir area. On the basis of D-InSAR technique analysis in ravine reservoir, how to eliminate the error and find the real moving area caused by rock and soil is the key problem. Considering the fact, an experiment region in reservoir of Wudongde hydropower station, Jinsha River has been studied. Based on D-InSAR analysis method and the characteristics of radar data, an analysis method of the SAR data trusted zone, the detectable landsliding displacement and error estimation has been established, extracting the effective range in the result of SAR data analysis.